To solve the equation \( x^2 + 2x - 8 = 0 \) by completing the square, follow these steps:
-
Start with the original equation: \[ x^2 + 2x - 8 = 0 \]
-
Move the constant term to the other side of the equation: \[ x^2 + 2x = 8 \]
-
Complete the square on the left side. To do this, take half of the coefficient of \( x \), square it, and add it to both sides. The coefficient of \( x \) is 2: \[ \left(\frac{2}{2}\right)^2 = 1 \] Add 1 to both sides: \[ x^2 + 2x + 1 = 8 + 1 \] \[ x^2 + 2x + 1 = 9 \]
-
Now, rewrite the left side as a square: \[ (x + 1)^2 = 9 \]
-
Take the square root of both sides: \[ x + 1 = \pm 3 \]
-
Solve for \( x \):
- If \( x + 1 = 3 \), then \( x = 2 \).
- If \( x + 1 = -3 \), then \( x = -4 \).
Thus, the solutions to the equation are: \[ x = 2 \quad \text{and} \quad x = -4 \]
So the correct answer is: x=2, x=−4 (or \( x \) equals 2, \( x \) equals negative 4).